La Sindrome delle Apnee Ostruttive del Sonno (OSAS) e i disturbi dell’umore in una popolazione di autotrasportatori / Obstructive Sleep Apnoea Syndrome and mood disorders in a population of public transport drivers - Ruberto, M.; Liotti, F. (La Medicina del Lavoro, 2011)
«Obstructive Sleep Apnoea Syndrome (OSAS) and mood disorders in a population of public transport drivers». Background: A growing number of reports pinpoint the high prevalence of mood disorders in OSAS patients. The aim of the study was to verify the presence of depressive mood disorders and their relationship with OSAS in a population of public transport drivers. Methods: 164 city bus drivers underwent an anthropometric and biochemical assessment, administration of ESS and Zung Scale questionnaires and cardio-respiratory polysomnography (PSG). The data were compared with a matched control group of 171 subjects. Results: The two groups of subjects differed as regards BMI (p